Measuring the Competitiveness of Islamic Banking in Indonesian Dual Banking System - Ir Ascarya; Diana Yumanita (Tazkia Islamic Finance and Business Review, 2008)
Islamic banks in many countries have emerged as important component of financial system that contributes to the growth and development of the country’s economy. They have proven to be a viable and competitive component of the overall financial system. In the dual banking system, Islamic banks have to be competitive to survive. One of the key to competitiveness is efficiency. This study will measure and compare the efficiency of Islamic and conventional banks in Indonesia using Data Envelopment Analysis (DEA) methodology. DEA is a non-parametric, deterministic methodology for determining the relative efficiency and managerial performance, based on the empirical data on chosen inputs and outputs of a number of decision making units. DEA allows us to compare the relative efficiency of banks by determining the efficient banks as benchmarks and by measuring the inefficiencies in input combinations (slack variables) in other banks relative to the benchmark. Intermediation approach will be applied. This study will identify the sources and level of inefficiency for each of the inputs and outputs of Islamic banks and conventional banks in Indonesia. The result shows that in overall, Islamic banking is relatively more efficient than conventional banking. This means that Islamic banks are competitive enough to compete with conventional banks. Islamic banking is technically more efficient, but less scale efficient than conventional banking. Internal inefficiency is the main source of disintermediation of conventional banking in Indonesia. Furthermore, accelerated expansion, organically and inorganically, is needed to improve scale and overall efficiencies of Islamic banking in Indonesia.Keywords: Banking, Islamic Banking, Efficiency, Data Envelopment Analysis